Manipulation of perovskite film by bias‐induced reversible lattice deformation toward tunable photoelectric performances - Lixia Ren (Wiley-VCH, 2021)
Abstract Organic lead halide perovskites have attracted extensive interest for potential use in next‐generation photovoltaic devices due to the demonstrated high power conversion efficiency, low materials cost, and low fabrication cost. Besides, the electromechanical properties have also been explored in detail to expand the application potential. Here, we report the reversible photoelectric modulation (including photoresponse and photoresistance modulation, by near 6%) in methylammonium lead triiodide (MAPbI3) film under an external electric bias (only 0.06 V µm‐1), which stems from the strain response induced by the competition of electrical biasing and light exposure. In addition, accompanied by the use of bias and light, the lattice is found to be deformed in MAPbI3 film. This result does not only shed light on the lattice deformation from external factors but also highlights the dramatic electron/photon‐lattice coupling in perovskite films.